(3cJGH aj Gdcfis - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf QHfG hQH BHGFfG GdChdjf CeG HYO aEfi deG LeYJ cJGHi ai CSeGA GdeYQhajf HGdcfG ef MUjdI GdYde hfbdI GdMOjK s
(3BNQgG (B:s
(3jfJgi CKfGA MQa GdhGh HHGH CHj GdhdjO hCNQ GdehLhO efg bhdg (B: (3hgh TjN eSJbje s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(143 (3b(B) s
Keywords: (3GdJGQjNs